Diagnóstico de la demanda del sistema energético de la Central Latacunga de CNT E.P. en base a la mejora de la calidad de energía usando la regulación del CONELEC N° 004/01. - Terán Espinosa, Diego Jacinto (2017)
The objective of the research work is about the quality of energy through the improvement of the electrical parameters, which in the technical part, has been affected the Latacunga CNT E.P. in its last months, for which the supplier (ELEPCO S.A.) has generated continuous fines, since they supply a balanced, sinusoidal voltage with constant amplitudes and frequencies. The increase in equipment within the study area has had a great technological development, especially in power electronics and telecommunications, which leads to a generation of events that affect the network in its technical parameters, which are mostly caused by nonlinear loads highly sensitive to variations in power supply, which has made it possible for the company to analyze its distribution circuits to improve the power quality parameters to avoid interruptions to operate free from disturbances in the electrical service. One of the objectives in the accomplishment of this thesis has been to find effective solutions to correct the events of variations of the electrical energy parameters that are presented in the electrical system. This work will focus on aspects of energy quality that are reduced by distortions of the waveform (Harmonics) and fluctuations of voltage (Flicker) with possible solutions currently used on the basis of data collection. The study will focus on Regulation No. CONELEC 004/01; and based on the measurements taken at the point that this regulation stipulates, improvements will be made based on simulations, which will give the necessary conclusions to maintain a good service in order to avoid the deterioration of the voltage signals and that leads to interruptions that cause the reduction or stop of processes that cause damages in the system.